ARDEN'S THEOREM FOR REGULAR EXPRESSIONS

  Identities for Regular Expression:-

Given R, P, L, Q as regular expressions, the following identities hold βˆ’

  • βˆ…* = Ξ΅
  • Ξ΅* = Ξ΅
  • RR* = R*R
  • R*R* = R*
  • (R*)* = R*
  • RR* = R*R
  • (PQ)*P =P(QP)*
  • (a+b)* = (a*b*)* = (a*+b*)* = (a+b*)* = a*(ba*)*
  • R + βˆ… = βˆ… + R = R (The identity for union)
  • R Ξ΅ = Ξ΅ R = R (The identity for concatenation)
  • βˆ… L = L βˆ… = βˆ… (The annihilator for concatenation)
  • R + R = R (Idempotent law)
  • L (M + N) = LM + LN (Left distributive law)
  • (M + N) L = ML + NL (Right distributive law)
  • Ξ΅ + RR* = Ξ΅ + R*R = R*
Arden's Theorem:-

In order to find out a regular expression of a Finite Automaton, we use Arden’s Theorem along with the properties of regular expressions.

Statement βˆ’

Let P and Q be two regular expressions.

If P does not contain null string, then R = Q + RP has a unique solution that is R = QP*

Proof βˆ’

R = Q + (Q + RP)P [After putting the value R = Q + RP]

= Q + QP + RPP

When we put the value of R recursively again and again, we get the following equation βˆ’

R = Q + QP + QP2 + QP3…..

R = Q (Ξ΅ + P + P2 + P3 + …. )

R = QP* [As P* represents (Ξ΅ + P + P2 + P3 + ….) ]

Hence, proved.
Assumptions for Applying Arden’s Theorem

  • The transition diagram must not have NULL transitions
  • It must have only one initial state

Method

Step 1 βˆ’ Create equations as the following form for all the states of the DFA having n states with initial state q1.

q1 = q1R11 + q2R21 + … + qnRn1 + Ξ΅

q2 = q1R12 + q2R22 + … + qnRn2

…………………………

…………………………

…………………………

…………………………

qn = q1R1n + q2R2n + … + qnRnn

Rij represents the set of labels of edges from qi to qj, if no such edge exists, then Rij = βˆ…

Step 2 βˆ’ Solve these equations to get the equation for the final state in terms of Rij

EXAMPLE:-

Construct a regular expression corresponding to the automata given below βˆ’

Finite Automata

Solution βˆ’

Here the initial state and final state is q1.

The equations for the three states q1, q2, and q3 are as follows βˆ’

q1 = q1a + q3a + Ξ΅ (Ξ΅ move is because q1 is the initial state0

q2 = q1b + q2b + q3b

q3 = q2a

Now, we will solve these three equations βˆ’

q2 = q1b + q2b + q3b

= q1b + q2b + (q2a)b (Substituting value of q3)

= q1b + q2(b + ab)

= q1b (b + ab)* (Applying Arden’s Theorem)

q1 = q1a + q3a + Ξ΅

= q1a + q2aa + Ξ΅ (Substituting value of q3)

= q1a + q1b(b + ab*)aa + Ξ΅ (Substituting value of q2)

= q1(a + b(b + ab)*aa) + Ξ΅

= Ξ΅ (a+ b(b + ab)*aa)*

= (a + b(b + ab)*aa)*

Hence, the regular expression is (a + b(b + ab)*aa)*.

Comments

Popular posts from this blog

PIGEONHOLE PRINCIPLE AND APPLICATIONS OF PUMPING LEMMA

EQUIVALENCE OF TWO FINITE AUTOMATAs